2023
DOI: 10.1002/gps.5977
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care navigation: A systematic review on different service types and their prevalence

Abstract: BackgroundDementia Care Navigators (DCNs) are professionals without clinical training, who provide individualised emotional and practical support to people living with dementia, working alongside clinical services. Navigator services have been implemented but the service offered vary without a consistent overview provided. The aim of this narrative systematic review was to describe and compare existing service formats, and to synthesise evidence regarding their implementation and impacts.MethodsThe review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Results of the current study indicate that these strategies to counter barriers to service accessibility and use are addressed by having FLC as integral members of rural memory clinics. Our findings are consistent with the recommendation that improving access to services requires dementia care navigators to be well integrated into health and social care systems [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the current study indicate that these strategies to counter barriers to service accessibility and use are addressed by having FLC as integral members of rural memory clinics. Our findings are consistent with the recommendation that improving access to services requires dementia care navigators to be well integrated into health and social care systems [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recent reviews of dementia navigation [ 28 , 29 ] have identified some positive outcomes related to service use but agree that there is not enough evidence to make substantial conclusions. Giebel et al [ 28 ] conclude that there is mixed evidence on effectiveness of care navigation, despite studies showing sizable benefits for some outcomes, and stress the need for more evaluation of impact on care utilization and in countries outside the USA which does not have universal health coverage. Kokorelias et al [ 29 ] concluded there is strong evidence for care navigation in delaying institutionalization and outcomes such as caregiver mastery, but weak evidence for health service use and functional independence.…”
Section: Introductionmentioning
confidence: 99%